2 GEORGE WASHINGTON PASCHAL, A DIGEST OF THE LAWS OF TEXAS: CONTAINING LAWS IN FORCE, AND THE REPEALED LAWS ON WHICH RIGHTS REST. CAREFULLY ANNOTATED. 1322 (3d ed. 1873) - (:unkn) unknown (General Publisher, 1873)
Prohibited entry into any church, religious assembly, school-room, or other place where persons are assembled for educational, literary, or scientific purposes, or into a ball room, social party, or other social gathering, composed of ladies and gentlemen, or to any election precinct on the day of an election, where people may be mustered for public duty or public assembly while armed with a Bowie-knife, dirk, butcher-knife, or any firearms known as a six-shooter, gun, or pistol of any kind. Violators guilty of a misdemeanor and fined not less than fifty nor more than five hundred dollars at the discretion of the court.
--
Keywords: SENSITIVE PLACES